Effect of Dexmedetomidine Added to Lidocaine Cartridge on the Level of Patient Sedation, Cooperation, and Patient and Surgeon Satisfaction during Mandibular Third-Molar Extraction Surgery: A Randomized Double-Blind Controlled Trial - Milad Etemadi Sh; Nasser Kaviani; Kimia Salimian; Golnaz Tajmiri (International Journal of Dentistry)
Background. Various methods have been introduced for anxiety control during third-molar extraction surgery. Dexmedetomidine (DEX) is known to have analgesic, anxiolytic, and sympatholytic properties with minimal adverse effects. This study aimed to evaluate the impact of the local injection of the combination of DEX and Lidocaine on patients’ anxiety and the surgeon’s satisfaction during third-molar extraction surgery. Methods. A total number of 26 healthy volunteers with symmetrical bilateral impacted mandibular third-molar teeth indicated for surgical removal were included in this double-blind randomized controlled trial. A single experienced surgeon performed two surgical extraction procedures within at least four-week time intervals using anesthetic cartridges containing “DEX + LIDO” or “LIDO alone” used randomly on each side for each patient. The Visual Analog Scale and the SDFQ index were used to evaluate patients’ anxiety and surgeon satisfaction during the procedure. Results. SDFQ reports showed that patients in the “DEX” group were 1.5 times more relaxed than those in the “LIDO alone” group. As a result, the level of sedation was considered statistically significant between the two groups (Wilcoxon test, P value <0.019). Wilcoxon test results also showed significant differences between the two groups regarding patients’ overall cooperation in terms of interfering movement and verbal presentation of discomfort (P value <0.05); however, this difference was not considered significant regarding nonverbal signs of discomfort (P value >0.05). Moreover, both the surgeon and the patients reported a significantly higher satisfaction rate in the DEX group (paired T-test, df = 25, P value <0.05). Conclusions. It was inferred from the outcomes of the present study that the application of DEX added to the LIDO local anesthesia cartridge could significantly benefit anxious patients with previous unpleasant dental treatment experiences. Trial Registration. This trial is registered with the clinical trial registration number: IRCT20200406046966N.